#Familygoals: Family influencers, calibrated amateurism, and justifying young digital labor - Abidin, Crystal (2017)
© The Author(s) 2017. Following in the celebrity trajectory of mommy bloggers, global micro-microcelebrities, and reality TV families, family Influencers on social media are one genre of microcelebrity for whom the “anchor” content in which they demonstrate their creative talents, such as producing musical covers or comedy sketches, is a highly profitable endeavor. Yet, this commerce is sustained by an undercurrent of “filler” content wherein everyday routines of domestic life are shared with followers as a form of “calibrated amateurism.” Calibrated amateurism is a practice and aesthetic in which actors in an attention economy labor specifically over crafting contrived authenticity that portrays the raw aesthetic of an amateur, whether or not they really are amateurs by status or practice, by relying on the performance ecology of appropriate platforms, affordances, tools, cultural vernacular, and social capital. In this article, I consider the anatomy of calibrated amateurism, and how this practice relates to follower engagement and responses. While some follower responses have highlighted concerns over the children’s well-being, a vast majority overtly signal their love, support, and even envy toward such parenting. I draw on ethnographically informed content analysis of two group of family Influencers on social media to illustrate the enactment and value of calibrated amateurism in an increasingly saturated ecology and, investigate how such parents justify the digital labor in which their children partake to produce viable narratives of domestic life.